Effect of Edible Coating Material Composition Based on Chitosan-Gelatin-CaCl2 and Cinnamon (Cinnamomum verum) Essential Oil on the Protection of Cocoa Beans (Theobroma cacao L.) During Storage - Putri, Aufy Nuraini; Soesantyo, Adi Kurnia; Iftitah, Elvina Dhiaul (Science and Technology Indonesia, 2025)
Chocolate, a highly demanded commodity, is derived from cocoa beans which undergo fermentation and drying to achieve a safe moisture content of up to 7.5% for storage. Storage conditions significantly impact cocoa bean quality. While edible coatings are commonly used to preserve food quality during storage, their application to cocoa beans using composite polymers and essential oils remains underexplored. This study aimed to evaluate the effectiveness of composite edible coatings, specifically chitosan-gelatinCaCl2 with cinnamon essential oil, in preserving cocoa bean quality over a 28-day storage period. Six variations of coating solutions were applied to peeled cocoa beans: K1= chitosan:gelatin 1:2 + CaCl2 1%, K2= chitosan:gelatin 1:2 + CaCl2 1% + 0.1% essential oil, K3=chitosan:gelatin 1:2 + CaCl2 1% + 0.3% essential oil, K4= chitosan:gelatin 2:1 + CaCl2 1%, K5= chitosan:gelatin 2:1 + CaCl2 1% + 0.1% essential oil, and K6= chitosan:gelatin 2:1 + CaCl2 1% + 0.3% essential oil, and K0 serving as a control without treatment. Quality parameters such as water content, fat content, and pH were analysed using ANOVA (α = 0.05). The results indicated that edible coatings significantly protected against changes in fat content but did not significantly affect water content or pH. The most effective treatment was K6, composed of chitosan:gelatin with the ratio of 2:1 + 1% CaCl2 + 0.3% cinnamon essential oil, providing optimal protection during storage.